Problems of forestry in Assam - Rajkhowa, S. (Indian Forester, 1986)
The problems relating to forestry in India have been discussed in the paper. After Independence, government ’khas’ forests land was given for non-forestry uses like agriculture, Reserve forests, too, have been falling victim to land grab by squatters. Unfortunately, vested political interests have contributed to this. The situation has reached a stage when all sections of society have to be enlightened about the importance of various categories of forests.